Aortic dissection and ruptures in adult congenital heart disease in Texas from 2009 to 2019. (11th October 2021) - Well, Andrew; Mizrahi, Michelle; Johnson, Gregory; Patt, Hanoch; Fraser, Charles D; Mery, Carlos M; Beckerman, Ziv
Abstract: : OBJECTIVES: Acute thoracic aortic dissection and rupture (TADR) has an incidence of 5–7 per 100 000-person years. Today, most children with congenital heart disease (CHD) survive to become adults with congenital heart disease (ACHD). This study evaluates TADR in patients with ACHD in a large, hospitalized patient population over 11 years to evaluate the incidence, risk factors and outcomes associated with TADR. METHODS: This was a retrospective review of the Texas Inpatient Discharge Data Set from 1 January 2009 to 31 December 2019. All non-trauma discharges of patients ≥18 years were included. ACHD discharges were identified by International Classification of Diseases, 9th edition (ICD-9)/10 diagnosis codes. TADR were identified using 2 definitions: TADR1 is an ICD-9/10 code for TADR, and TADR2 is TADR1 with an ICD-9/10 procedure code for aortic intervention. Descriptive, univariate and logistic regression statistics were used. RESULTS: A total of 22 154 664 eligible discharges were identified, of which 12 584 (0.06%) were TADR1 and a subgroup of 5699 (0.03%) were TADR2. CHD was more prevalent in TADR1 (0.2% vs 0.05%; P < 0.001) and TADR2 (0.3% vs 0.04%; P < 0.001). Adjusting for known TADR risk factors, CHD had an odds ratio of 1.69 (95% confidence interval: 1.09–2.63; P = 0.020) for TADR1 and an odds ratio of 1.69 (95% confidence interval: 0.99–2.88; P = 0.056) for TADR2. No in-hospital deaths were found in patients with CHD with TADR. CONCLUSIONS: ACHD discharges had a higher frequency of TADR versus the general population (0.9–1.2 vs 0.3–0.6 per 1000 discharges). There is an indication that CHD confers an increased adjusted odds of TADR. As the ACHD population continues to grow in number as well as age, it will be important to continue to assess the risk of TADR from CHD and how traditional risk factors impact this risk. Abstract : Acute thoracic aortic dissection is a devastating disease with a reported incidence of 5–7 cases per 100 000 person-years in the general population [1, 2].